Cilia distal domain: diversity in evolutionarily conserved structures - Soares, Helena (2019)
Eukaryotic cilia are microtubule-based organelles that protrude from the cell surface to fulfill sensory and motility functions. Their basic structure consists of an axoneme templated by a centriole/basal body. Striking differences in ciliary ultra-structures can be found at the ciliary base, the axoneme and the tip, not only throughout the eukaryotic tree of life, but within a single organism. Defects in cilia biogenesis and function are at the origin of human ciliopathies. This structural/functional diversity and its relationship with the etiology of these diseases is poorly understood. Some of the important events in cilia function occur at their distal domain, including cilia assembly/disassembly, IFT (intraflagellar transport) complexes' remodeling, and signal detection/transduction. How axonemal microtubules end at this domain varies with distinct cilia types, originating different tip architectures. Additionally, they show a high degree of dynamic behavior and are able to respond to different stimuli. The existence of microtubule-capping structures (caps) in certain types of cilia contributes to this diversity. It has been proposed that caps play a role in axoneme length control and stabilization, but their roles are still poorly understood. Here, we review the current knowledge on cilia structure diversity with a focus on the cilia distal domain and caps and discuss how they affect cilia structure and function.